A modified Density-Based Scanning Algorithm with Noise for spatial travel pattern analysis from Smart Card AFC data. (September 2015) - Kieu, Le-Minh; Bhaskar, Ashish; Chung, Edward
Highlights: Spatial travel pattern analysis of individual passenger. New algorithm WS-DBSCAN to detect & update spatial travel pattern. A numerical experiment using observed AFC data. Abstract: Smart Card Automated Fare Collection (AFC) data has been extensively exploited to understand passenger behavior, passenger segment, trip purpose and improve transit planning through spatial travel pattern analysis. The literature has been evolving from simple to more sophisticated methods such as from aggregated to individual travel pattern analysis, and from stop-to-stop to flexible stop aggregation. However, the issue of high computing complexity has limited these methods in practical applications. This paper proposes a new algorithm named Weighted Stop Density Based Scanning Algorithm with Noise (WS-DBSCAN) based on the classical Density Based Scanning Algorithm with Noise (DBSCAN) algorithm to detect and update the daily changes in travel pattern. WS-DBSCAN converts the classical quadratic computation complexity DBSCAN to a problem of sub-quadratic complexity. The numerical experiment using the real AFC data in South East Queensland, Australia shows that the algorithm costs only 0.45% in computation time compared to the classical DBSCAN, but provides the same clustering results.